Pd(II)-catalyzed tandem cycloannulative-alkenylation of o-alkynyl-phenols/anilines with (E)-β-Iodovinyl sulfones: a direct strategy to construct 3-(Vinyl sulfonyl)benzoheterole derivatives - Reddy, Raju Jannapu; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2023)
Benzoheterolesand vinyl sulfones are the most promisingpharmaceuticalrelevance motifs, yet the hybrid analogues of these scaffolds stillneed to be explored. We report herein a general and highly efficientPd(OAc)(2)-catalyzed intramolecular cyclization and vinylationof o-alkynylphenols/o-alkynylanilineswith (E)-beta-iodovinyl sulfones under mild reactionconditions. A direct C(sp(2))-C(sp(2)) cross-couplingis enabled for the diversity-oriented synthesis of vinyl sulfone-tetheredbenzofurans and indoles in good to high yields with excellent stereoselectivity.Notably, this tandem process was consistent at the gram scale, andin situ, generation of 2-(phenylethynyl)phenol has also been utilizedin a scalable synthesis. Late-stage synthetic transformations werealso further explored, including isomerization and desulfonylative-sulfenylation.Moreover, several control experiments were accomplished, and we proposeda plausible mechanism based on existing experimental results.